A Review on Role of Image Processing Techniques to Enhancing Security of IoT Applications - Al-Ghaili A.M.; Gunasekaran S.S.; Jamil N.; Alyasseri Z.A.A.; Al-Hada N.M.; Ibrahim Z.-A.B.; Bakar A.A.; Kasim H.; Hosseini E.; Omar R.; Kasmani R.M.; Razali R.A. (Institute of Electrical and Electronics Engineers Inc., 2024)
Once an image has been processed by, for example, a robot machine, for the purpose of, for example, features extraction or meaningful information retrieval, has a secure scheme been applied to preserve security and privacy of such information before sending it to another processing party? A huge number of image-related Internet of Things (IoT) applications face such an issue. But what are applied and potentially being applied image processing techniques that have contributed to enhance the security and privacy of IoT applications? There are numerous IoT applications that utilize image processing techniques in this direction. This article aims to survey and review a number of recently published papers and research studies that encompass proposed methods in which image processing techniques are applied to enhance the security, privacy, and safety of IoT applications. It also aims to help interested researchers in related fields have insights on what the role of image processing in enhancing the security of IoT applications is and what those techniques applied to enhance the security of IoT applications are. A comprehensive framework has been graphically extracted to give readers in the field of IoT security a map with the suitable image processing techniques that serve better to enhancing IoT applications in terms of security and privacy. 2013 IEEE.